2011
DOI: 10.4103/1319-3767.77247
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of duodenal injuries: A comprehensive overview

Abstract: Background/Aim:Duodenal injury is an uncommon finding, accounting for about about 3 – 5% of abdominal trauma, mainly resulting from both penetrating and blunt trauma, and is associated with significant mortality (6 - 25%) and morbidity (30 - 60%).Patients and Methods:Retrospective analysis was performed in terms of presentation, management, morbidity and mortality on 14 patients of duodenal injuries out of a total of 172 patients of abdominal trauma attending Subharti Medical College.Results:Epigastric pain (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 10 publications
4
24
0
2
Order By: Relevance
“…Isolated duodenal injuries are rare. Duodenal injuries often occur together with other organ injuries and damages to large vessels [34].…”
Section: Traumamentioning
confidence: 99%
“…Isolated duodenal injuries are rare. Duodenal injuries often occur together with other organ injuries and damages to large vessels [34].…”
Section: Traumamentioning
confidence: 99%
“…Assensio et al 2 describe that liver injury (16.9%) is most commonly associated to duodenal injury, followed by pancreatic injury (11.6%), small intestine (11.5%), and colon (11.3%). According to Pandey et al, 11 the liver is the organ most affected, followed by colon (43%) and pancreas (14%). In this study, the associated injuries observed were most prevalent in the liver and small intestine with incidence of both of 45.45%.…”
Section: Discussionmentioning
confidence: 97%
“…The treatment of duodenal lesions varies according to the severity of each individual case, and can involve anything from primary closure to a Whipple procedure. 11,12 However, according to Ordonez et al 6 , in more severe cases, mainly those associated with multiple organ injuries & hemodynamic instability (accounting for 25% of deaths -hypovolemic shock) it is recommended to perform damage control surgery briefly in order to put the patient in a better position for definitive treatment. Primary duodenal repair is the main intervention in this study (90.9%), as described in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…El hígado fue el ó rgano má s comú nmente dañ ado, con un total de 600 lesiones ocurridas con una frecuencia del 17%. Otros ó rganos incluyeron el colon con 462 (13%), el pá ncreas con 408 (12%), el intestino delgado con 395 (11%), el estó mago con 323 (9%) y las lesiones vasculares (arterial y venoso) con 536 (15%) 3,4,6-13,17,19-22,24-26 . Localizació n anató mica de la lesió n Para identificar la localizació n anató mica de mayor frecuencia se revisaron 15 series publicadas 2,6,7,[10][11][12][13][14][15]19,21,22,[24][25][26] 6 , 1975 (22) 17 (1%) 5 (0,3%) Lucas y Ledgerwood 8 , 1975 (36) 0 36 (2%) Matolo et al 9 , 1975 (32) 19 (1,1%) 13 (0,8%) Kelly et al 2 , 1978 (34) 28 (1,6%) 6 (0,3%) Stone y Fabian 10 , 1979 (321) 294 (16,7%) 27 (1,5%) Flint et al 11 , 1979 (75) 56 (3,2%) 19 (1,1%) Snyder et al 12 , 1980 (228) 180 (10,2%) 48 (2,7%) Levinson et al 50 , 1982 (93) 74 (4,2%) 19 (1,1%) Adkins y Keyser 13 , 1984 (56) 39 (2,2%) 17 (1%) Fabian et al 14 , 1984 (10) 0 10 (0,6%) Ivatury et al 15 , 1985 (100) 100 (5,7%) 0 Bostman et al 16 , 1989 (22) 16 (1%) 6 (0,3%) Cogbill et al 17 , 1990 (164) 102 (5,8%) 62 (3,5%) Cuddington et al 18 , 1990 (42) 16 (1%) 26 (1,5%) Timaran et al 19 , 1999 (152) 152 (8,6%) 0 Jen-Feng Fang et al 20 , 1999 (18) 0 18 (1%) Jansen et al 21 , 2002 (30) 27 (1,5%) 3 (0,2%) Seamon et al 22 , 2007 (29) 29 (1,6%) 0 Rathore et al 23 , 2007 (23) 16 (1%) 7 (0,4%) Pereira et al 24 , 2008 (8) 5 (0,3%) 3 (0,2%) Girgin et al 25 , 2009 (67) 59 (3,4%) 8 (0,5%) Sanjai et al 26 , 2011 (14) 8 (0,5%) 6 (0,3%) Total (1.760) 1400 (80%) 360 (20%) c i r e s p . 2 0 1 4 ; x x ( x x ) : x x x -x x x analiza...…”
Section: Lesiones Asociadasunclassified